STIMULASI DETEKSI INTERVENSI DINI TUMBUH KEMBANG ANAK BAGI GURU PAUD/RA KABUPATEN MAGETANSTIMULATION, DETECTION, AND INTERVENTION FOR CHILD GROWTH AND DEVELOPMENT FOR EARLY CHILDHOOD EDUCATION (PAUD/RA) TEACHERS IN MAGETAN REGENCY - Tinuk Esti Handyani; Agung Suharto; Tutiek Herlina; Nana Usnawati; Nuryani Nuryani; Astuti Setuyani; Sulikah Sulikah; Astin Nur Hanifah; Nurlailis Sa’adah; Rahayu Sumaningsih; Nurweningtyas Wisnu; Triana Septianti Purwanto (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Background: Stimulation, Early Detection, and Early Intervention for Child Growth and Development (SDIDTK) is an essential strategy for identifying developmental deviations at an early stage, enabling timely intervention. Early childhood teachers play a strategic role in implementing SDIDTK but require adequate competency through technical training. Objective: To analyze the effectiveness of SDIDTK Technical Guidance (Bimbingan Teknis/Bimtek) in improving the knowledge of PAUD/RA teachers in Magetan Regency. Methods: A one-group pretest–posttest design was conducted involving 71 PAUD/RA teachers participating in a two-day technical training. Data were analyzed descriptively and using the Wilcoxon Signed Rank Test. Results: The proportion of participants with good knowledge increased from 5.64% to 63.38%, while poor knowledge decreased from 74.64% to 0%. Overall, 92.96% of participants demonstrated improved scores, with a statistically significant difference (p < 0.001). Conclusion: SDIDTK technical training effectively improved teachers' knowledge and has the potential to strengthen SDIDTK implementation and early identification of child growth and developmental disorders.